Ecologias das práticas pedagógicas: (per)cursos narrativos de experiências em educação em direitos humanos - Nascimento, Vânia Virgens Almeida (Universidade do Vale do Rio dos Sinos, 2024)
This thesis aims to analyze how the pedagogical practices of women actively engaged in Public Education reflect experiences in Education in Human Rights (hereafter referred to as EHR) in the city of Salvador. To conduct this analysis, it was necessary to establish theoretical foundations through the curation of scientific works on Education in Human Rights; explore the life and professional (per)courses of women involved in Public Education in Salvador; and identify their authored and authorized pedagogical practices, as well as their connections to EHR principles and dimensions. Methodologically, this research adopts a qualitative approach, employing narrative interviews as its primary method. These narratives were supported by summaries produced by the women and by the analysis of their described pedagogical practices. The analysis enabled the identification of significant elements within the life and professional (per)courses of these women, revealing how their pedagogical practices — whether formal or informal — embody EHR principles and dimensions. Anchored in the theoretical perspective of complexity and ecologies of pedagogical practices, the theoretical framework draws upon contributions from the following scholars: Candau (1995, 2008, 2012, 2013), Carbonari (2011, 2015), Dallari (2004), Freire (1987, 1989, 1996), Marinho (2012), Monteiro (2013), Sacavino (2008), Yúdice (2012), and Viola (2010, 2013). The biographical trajectories, characterized by empowerment and democratic advocacy through pedagogical practices, revealed that the dimensions of fostering individuals as rights-bearing subjects, supporting empowerment processes, and promoting social change and transformation are actively present — although not explicitly labeled as Education in Human Rights. The findings suggest that the ecology of pedagogical practices highlights the dissemination of knowledge and ways of rethinking education and humanity as pivotal elements for fostering a strengthened pedagogy in EHR.
Keywords: Práticas pedagógicas; Educação em direitos humanos; Ecologias; Mulheres engajadas; Educação básica; Educação pública; Pedagogical practices; Education in human rights; Ecologies; engaged women; Basic education; Public education; ACCNPQ::Ciências Humanas::Educação